Laundry Detergency of Solid Nonparticulate Soil or Waxy Solids: Part II. Effect of the Surfactant Type. Issue 3 (4th January 2019) - Chanwattanakit, Jarussri; Scamehorn, John F.; Sabatini, David A.; Chavadej, Sumaeth
Abstract: In this work, methyl palmitate with a melting point around 30°C was used as a model of waxy soil. Its detergency was evaluated with a hydrophilic surface (cotton) or a hydrophobic surface (polyester) using different surfactants: alcohol ethoxylate (EO9), sodium dodecyl sulfate (SDS), methyl ester sulfonate (MES), methyl ester ethoxylate (MEE), and two extended surfactants (C12, 14 ‐10PO‐2EO‐SO4 Na and C12, 14 ‐16PO‐2EO‐SO4 Na). The detergency efficiency at a 0.2 wt.% surfactant and 5 wt.% NaCl gradually increased while redeposition gradually decreased with increasing washing temperature in most studied surfactant solutions; this was observed both above and below the melting point of methyl palmitate on both studied fabrics. If the methyl palmitate was heated above the melting point when deposited on the fabric, it was better able to penetrate into the fabric matrix as compared to deposition below the melting point, resulting in poorer detergency for heated deposition, particularly for washing temperatures lower than the melting point. Among the surfactants studied, the nonionic surfactant (EO9) showed the highest detergency efficiency (73–94%) at any washing temperature especially on the polyester fabric. For washing temperatures below the melting point, detergency performance correlated well with the contact angle of surfactant solution on the solid methyl palmitate surface for all studied surfactants when salinity was varied. In this work, conditions resulting in the highest detergency below the melting point corresponded to the highest detergency above the melting point, suggesting this as a systematic approach to formulating below the melting point of the soil. Charge of particles or fabric was not observed to be important to the detergency mechanism, but steric factors resulting from surfactant adsorption were observed to be important mechanistic factors in waxy solid detergency.